Matrizes luso-europeias na formação do constitucionalismo brasileiro: reflexos na prestação jurisdicional contemporânea - Sessa, Márcio de (2014)
This research aims to investigate the epistemological arrays that organized the concept of constitutionalism and power in Brazil during the process of Independence that took place in 1822 as well as try to identify consequences of these matrices in contemporary jurisdictional service. However, it was necessary to understand a historical foray into the place of Latin America in the Constitution of Modernity, from the age of discovery, to understand the elements of Eurocentrism (Dussel) and modern thought Abyssal (Bonaventure) moving to the Brazilian colony with the Royal Family in 1808, phenomenon which was crucial to the breakup of the colonial pact with Porto Revolution and Independence of Brazil. For these philosophies and historical assumptions, it analyzes the characteristics of the organized constitutionalism and liberalism in Brazil, which had in Coimbra the intellectual matrix for the creation of a political elite for the nascent Empire. The legal basis was analyzed in two parts, the first one is the supported administrative jurisdiction in the State Council, which is auxiliary of the moderator power, responsible for legal cultural production and also the Supreme Court, empowered to review decisions to revoke and isolated from the "political" conflict between the powers. In addition it holds the analysis of the reorganization of power with the Republican Constitution of 1891, when the new institutional model empowered the review of decisions, the arbiter of conflicts between the powers and opened the jurisdictional control of constitutionality through the diffuse means and the Supreme Court assumed the power of last interpret of the Constitution. Finally, we identify the reflections of contemporary adjudication constitutional basis, organized state power and justice and which can propose hypotheses about the phenomena of the